Analysis of the pattern of suprahyoid muscle activity during pharyngeal swallowing of foods by healthy young subjects - Ashida, I.; Iwamori, H.; Kawakami, S.-Y.; Miyaoka, Y.; Murayama, A. (Journal of medical engineering & technology, 2010)
We previously developed the TP technique to discriminate between the activity patterns of skeletal muscles. In this study we aim to identify the TP value(s) that can be used to sensitively evaluate the activity patterns of the suprahyoid (SH) muscles during swallowing. We also analyse the effect of food textural properties on the activity patterns of the SH muscle during oral and pharyngeal swallowing. Three test foods consisting of 3%, 6% and 9% of a thickening agent, Mousse-up (MU) were prepared. Their textural properties differed significantly. Swallowing of 9% MU involved a significantly longer average duration than 3% MU. The average T50 value for 6% MU was significantly larger than that for 3% MU. However, the average T20 and T80 values of the test foods did not differ. Thus, the T50 value is particularly suitable for evaluating SH muscle swallowing patterns. Moreover, test foods that vary in their textural properties elicit different durations and patterns of SH muscle activity.